KONTRIBUSI INDONESIA DALAM PENGIRIMAN PASUKAN PERDAMAIAN PADA MISI MARITIME TASK FORCE (MTF) UNITED NATIONS INTERIM FORCE IN LEBANON (UNIFIL) - Salsa Desliana Alya Putri; Saiman Pakpahan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The conflict that occurred in Lebanon in 2006 caused civilian and military casualties as well as the destruction of civilian infrastructure and massive displacement due to Israeli attacks on countries in the Middle East. The United Nations formed a peacekeeping operation, namely the United Nations Interim Force In Lebanon (UNIFIL) with the aim of maintaining peace in Lebanon. This study uses qualitative methods with data collection methods in the form of documentary studies. Documentary studies are conducted by collecting and analyzing written documents or pictures from interviews. This study uses the Neorealist Perspective and the theory of Naval Diplomacy. This theory explains naval diplomacy in Maritime Task Force missions.. Indonesia has a global vision as stated in the fourth paragraph of the Preamble to the 1945 Constitution, namely